Editorial statement: Ten years of life of EJGE - José Manuel Sánchez-Santos; Giacomo Benedetto (European Journal of Government and Economics (EJGE), 2022)
In this editorial statement, we present a balance of the first decade of life of the European Journal of Government and Economics. We discuss the main difficulties an independent journal faces in maintaining the policy of open access and publication free of charge. We also renew the commitment to the journal's spirit, particularly with the editorial rigour and best practices. Finally, we identify the next steps in the consolidation of EJGE as an academic journal that attempts to keep an integrated approach between the fields of political science and economics.
Keywords: 330; academic journal; economics; indexing; open access; political science